Land-based spirituality among the Cree of the Mushkegowuk territory. Issue 1 (2nd January 2016) - Dylan, Arielle; Smallboy, Bartholemew
ABSTRACT: This article reports on findings from a research project investigating social, cultural, political, community, and spiritual impacts of a mining development sited in the Mushkegowuk territory of the coastal Cree people of western James Bay. When using a variety of indicators to explore how the negotiated agreement with an industrial proponent (diamond mining) was impacting community members, the threat to cultural lifeways and contingent spirituality as a result of land degradation was expressed by most participants in the study. While mindfulness, as adopted from the Buddhist tradition, denotes a very specific type of practice involving present-moment awareness, the breath, and body sensations, mindfulness in its broader definition refers more generally to a state of keen awareness. Across two phases of this research project, representing qualitative interviews with more than 50 participants, a picture of deep relationship and engagement with the land and its myriad life forms emerged, a picture suggestive of profound awareness, attunement, and reciprocity consistent with the broader definition of mindfulness. It is upon this land-based relationship that spirituality for the Mushkegowuk Cree people relies, and, as expressed by many study participants, the very core of their identity is founded on this form of spirituality.